Therapeutic Vesicular Nanoreactors with Tumor‐Specific Activation and Self‐Destruction for Synergistic Tumor Ablation. Issue 45 (4th October 2017) - Li, Junjie; Dirisala, Anjaneyulu; Ge, Zhishen; Wang, Yuheng; Yin, Wei; Ke, Wendong; Toh, Kazuko; Xie, Jinbing; Matsumoto, Yu; Anraku, Yasutaka; Osada, Kensuke; Kataoka, Kazunori
Abstract: Polymeric nanoreactors (NRs) have distinct advantages to improve chemical reaction efficiency, but the in vivo applications are limited by lack of tissue‐specificity. Herein, novel glucose oxidase (GOD)‐loaded therapeutic vesicular NRs ( thera NR) are constructed based on a diblock copolymer containing poly(ethylene glycol) (PEG) and copolymerized phenylboronic ester or piperidine‐functionalized methacrylate (P(PBEM‐ co ‐PEM)). Upon systemic injection, thera NR are inactive in normal tissues. At a tumor site, thera NR are specifically activated by the tumor acidity via improved permeability of the membranes. Hydrogen peroxide (H2 O2 ) production by the catalysis of GOD in thera NR increases tumor oxidative stress significantly. Meanwhile, high levels of H2 O2 induce self‐destruction of thera NR releasing quinone methide (QM) to deplete glutathione and suppress the antioxidant ability of cancer cells. Finally, thera NR efficiently kill cancer cells and ablate tumors via the synergistic effect. Abstract : Double action : Glucose oxidase (GOD)‐loaded vesicular nanoreactors are prepared from a diblock copolymer, which can be activated by tumor acidity to produce H2 O2 increasing tumor oxidative stress. High levels of H2 O2 also induce self‐destruction of the vesicles releasing quinone methide to deplete glutathione and suppress the antioxidant ability of cancer cells. This synergistic effect of the nanoreactors results in efficient cancer‐cell killing and tumor ablation.